1999
DOI: 10.1001/archderm.135.3.269
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma and Tumor Thickness

Abstract: Objective: To test the basic assumption of campaigns for early diagnosis of melanoma, ie, prognosis is correlated with the delay in the diagnosis. Design: Prospective study of the correlation between delays to diagnosis, assessed using a questionnaire, and the Breslow thickness as a prognosis marker. Setting: Dermatology departments in France. Patients: Fivehundredninetyconsecutivepatients,referred within 12 weeks after resection of cutaneous melanoma. Main Outcome Measures: Assessment of 5 successive time int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(31 citation statements)
references
References 12 publications
(20 reference statements)
3
26
1
1
Order By: Relevance
“…17 Multiple factors seem to contribute to the development of thick melanoma, including factors intrinsic to NM and those intrinsic to the elderly. There is now evidence 25 to suggest that NM grows more rapidly, possessing greater biological "aggressivity" than other tumor types. It is established that NM has a poorer prognosis than SSM, but in a large study of prognostic factors, 26 this was attributed to thickness alone.…”
Section: Commentmentioning
confidence: 99%
“…17 Multiple factors seem to contribute to the development of thick melanoma, including factors intrinsic to NM and those intrinsic to the elderly. There is now evidence 25 to suggest that NM grows more rapidly, possessing greater biological "aggressivity" than other tumor types. It is established that NM has a poorer prognosis than SSM, but in a large study of prognostic factors, 26 this was attributed to thickness alone.…”
Section: Commentmentioning
confidence: 99%
“…Nodular melanoma tends to follow a more aggressive clinical course than the superficial spreading subtype [24], lacking a precancerous or “ in situ ” phase, whilst desmoplastic melanomas generally carry a better prognosis, tending to present with localized disease [25, 26]. The biology of all melanomas may not be the same: nodular melanomas are also believed to progress rapidly [27]. This means that a similar interval between symptom onset and presentation could result in differences in tumour thickness related to the biological behaviour of the tumour [27].…”
Section: Discussionmentioning
confidence: 99%
“…The biology of all melanomas may not be the same: nodular melanomas are also believed to progress rapidly [27]. This means that a similar interval between symptom onset and presentation could result in differences in tumour thickness related to the biological behaviour of the tumour [27]. It was not possible to determine whether or not delay was influenced by melanoma-specific features, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies exploring the earliest clinical manifestation of nodular melanomas, which are more often small in diameter, regular in shape and even in color, and frequently amelanotic, a strict histologic definition is observed. Although it may prove nearly impossible to detect rapidly growing nodular melanoma, invasive from the outset and biologically aggressive nodular melanomas at thicknesses that pose minimal risk to the patient, early detection will be achieved only with greater awareness of this clinically distinct subtype 6 . Certainly, we previously indicated that nodular melanomas may be detected at an early point, 7 albeit rarely.…”
Section: To the Editormentioning
confidence: 97%